Development of Basic Computer Subjects in Teaching and Learning by Using Video for Students at Faculty of Education, Souphanouvong University - THIPPHAPHONE, Kinnaly; SILIVANH, Sommay; PANFONGPHET, Sipaseuth; PHATHOUMVANH, Phanthamanath (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
This research is to study the development of basic computer Subject in teaching and learning by using video for students at Faculty of Education, Souphanouvong University, the objectives of this research are to create teaching aids for basic computer subject by using video, to study the efficiency of teaching plans which was based on the criteria of 85/85, to study students learning outcomes and to study the students’ satisfaction with teaching and learning by using video, The sample group selected for this study was one class, which consisted of 19 students, class 2CH. The instruments of this research consisted of 10 teaching plans with 90 minutes each, there were 30 topics of video for teaching. Sub-test, post-test and satisfaction questionnaires were used to evaluate the quality of teaching by using video and instruments were marked by experts to evaluate the quality of questions, and the Index of Item Objective (IOC) ranged from 0.66 to 1.00 and the reliability of questionnaires was 83.40%. The research results were as follows: teaching aid were created in one series of videos for teaching basic computer (Microsoft Excel 2013), teaching plans for teaching basic computers by using videos for students at Faculty of Education, Souphanouvong University were 86.89/90.00 which was higher than the criteria set at 85/85, the effectiveness index value of students coming from videos for learning basic computers was at an excellent level, and students were satisfied with teaching and learning basic computers by using video for students at the Faculty of Education was at a high level.